Between the «ideal-widow» and the «royal-widow»: Representation about widowhood in a text from El Recreo - Huamán Durand, Rubí (2024)
The topic of the widow in literature and in the Peruvian press of the nineteenth century has not been the subject of study, although it is of great importance to understand the historical development of female representations. For this reason, the present research has the purpose of approaching the construction of the figure of widows in a publication of the Cuzco newspaper El Recreo (1876-1877). It is intended to demonstrate that the article «La viuda» (1876) by Ramón Matto is linked to the Judeo-Christian and Spanish tradition that criticizes widows' remarriage and, in this way, perpetuates a stereotypical view of this female group.